Pelatihan Teknik Budidaya Sayuran Sederhana bagi Guru PAUD sebagai Upaya Penguatan Pembelajaran Berbasis Alam - Diantifani Rizkita; Fitria Ulfah; Eri Sundari (Universitas Garut, 2026)
Nature-based learning is an effective approach to stimulating the holistic development of early childhood. However, its implementation in early childhood education (PAUD) units still faces challenges, particularly limited teacher competency in integrating the environment as a learning resource. This study aims to analyze the effectiveness of training in simple vegetable cultivation techniques for PAUD teachers in strengthening nature-based learning. The method used was a qualitative approach with a case study design among PAUD teachers in the Cisarua area, West Bandung Regency. Data were collected through observation, interviews, and documentation during the training and implementation activities. The results showed that the training improved teachers' understanding of cultivation techniques (land preparation, planting, fertilization, and maintenance) and their ability to design contextual, environment-based learning. Furthermore, vegetable cultivation activities have been shown to support children's cognitive, motor, social-emotional, and environmental awareness development. Therefore, this training is an effective strategy for integrating environmental education into PAUD learning practices. Keywords: PAUD, nature-based learning, vegetable cultivation, teacher training, garden-based learning